Effect of biochar and compost application on kailan yield (Brassica oleraceae) - Finda Novrian; Mardhiah Hayati; . Zaitun; . Chairunas (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The objective of experiment was to study effect of biochar and compost application on the best yield of kalian.  The research was conducted at Field Experiment of Provincial Agricultural Service (BPTP), Aceh Province.  The experimental arranged in a randomized complate block design with two factors and four replications.  Biochar consisted of two levels, i.e. without biochar and with biochar 30 ton ha-1. Compost consisted of two levels, i.e. without compost and compost 30 ton ha-1.  The result showed that biochar application affected significantly to stem diameter 7 DAP and not significant to number of leaves and plant height 7, 14, 21, 28 DAP, stem diameter 14, 21, 28 DAP, the 6th of length and width leaf and plant fresh weight.  Compost application affected significantly to number of leaves 14 DAP and the 6th of length leaf; and highly significant to number of leaves 7, 21, 28 DAP, plant height 7, 21, 28 DAP, stem diameter 7, 14, 21, 28 DAP, the 6th of width leaf and plant fresh weight, but not significant to plant height 14 DAP.  There was significantly interaction between biochar and compost application to stem diameter 7 DAP.  There were not interaction to number of leaves and plant height 7, 14, 21, 28 DAP, stem diameter 14, 21,28 DAP, the 6th of length and width leaf and plant fresh weight.